An Autopsy Case of Rapidly Aggravated Clostridium perfringens Septicemia with Colorectal Cancer. (30th September 2022) - Kohya, Risako; Murai, Taichi; Taguchi, Yudai; Sawai, Kyohei; Takehara, Masaya; Nagahama, Masahiro; Itaya, Kazufumi; Koike, Yuta; Endo, Ayana; Ono, Yuji; Nagasaka, Atsushi; Nishikawa, Shuji; et al.
Abstract : This report presents a case of a 60-year-old man who was diagnosed with ascending colon cancer with metastases of the lymph nodes and multiple liver metastases. Three days before the introduction of the first chemotherapy, he visited our hospital due to high fever. The blood test revealed an increase in the inflammatory response, hepatobiliary enzyme level, lactate dehydrogenase (LDH) level, and renal function deterioration. Contrast-enhanced computed tomography (CT) showed a rapid progression of primary lesion and liver metastatic lesions. Treatment with 5-fluorouracil, leucovorin, and oxaliplatin and cetuximab (FOLFOX/Cmab) was initiated, and the patient was admitted to our hospital after the first day of chemotherapy. At midnight, he had chills, red urine, and rapid hypoxemia. The second blood test showed progression of anemia; increased total bilirubin, aspartate aminotransferase, and LDH levels; and decreased platelet and fibrinogen levels. The serum was red wine in color, indicating marked hemolysis. The respiratory condition rapidly deteriorated, and tracheal intubation was performed and transferred into the intensive care unit. However, blood oxygenation did not increase, and the patient died the next morning, 19 h after admission, despite intensive care. Postmortem CT showed intraperitoneal free air and gas retention in the liver tumor and portal vein system. Pathological autopsy revealed perforation in ascending colon cancer, many Gram-positive rods in the perforation site, dissemination of bacteria throughout the body, and diffuse pulmonary edema. Subsequently, blood cultures reported Clostridium perfringens (CP), which is a product of alpha-toxin. CP infection can cause rapid aggravation and sudden death. The physicians should be aware of this highly fatal infection, leading to immediate diagnosis and treatment.